2019
DOI: 10.1136/bmjgh-2018-001241
|View full text |Cite
|
Sign up to set email alerts
|

Estimating global trends in total and childhood antibiotic consumption, 2011-2015

Abstract: IntroductionUnderstanding patterns of antibiotic consumption is essential to ensure access to appropriate antibiotics when needed and to minimise overuse, which can lead to antibiotic resistance. We aimed to describe changes in global antibiotic consumption between 2011 and 2015.MethodsWe analysed wholesale data on total antibiotic sales and antibiotics sold as child-appropriate formulations (CAFs), stratified by country income level (low/middle-income and high-income countries (LMICs and HICs)). The volume o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 38 publications
(52 reference statements)
1
52
0
Order By: Relevance
“…[ 2 ] Antibiotic usage rates are highest for young children. [ 17–24 ] Young children, at critical developmental stages, are commonly exposed to antibiotics in low‐income settings. As reported from a large longitudinal household‐based study, children from eight LMIC countries consumed an average of 4.9 antibiotics courses annually during the first two years of life.…”
Section: Antibiotic Consumption and Variation In Overall Usementioning
confidence: 99%
“…[ 2 ] Antibiotic usage rates are highest for young children. [ 17–24 ] Young children, at critical developmental stages, are commonly exposed to antibiotics in low‐income settings. As reported from a large longitudinal household‐based study, children from eight LMIC countries consumed an average of 4.9 antibiotics courses annually during the first two years of life.…”
Section: Antibiotic Consumption and Variation In Overall Usementioning
confidence: 99%
“…Some studies have used pharmaceutical sales data, which reflect the antibiotic consumption of whole countries rather than individuals or communities. 5,30,31 Nevertheless, despite the different data sources used, the proportion of prescribed antibiotics that were access antibiotics was broadly similar across paediatric studies. One international study found that 76.0% of all antibiotics used were access antibiotics (compared with 72.4% in our study) and 30.7% were amoxicillin (compared with 33.9% in our study).…”
Section: Researchmentioning
confidence: 99%
“…For example, in our study, amoxicillin with clavulanic acid was available at only 17.4% of health facilities, whereas recent global pharmaceutical sales data indicate it is used in almost equal amounts to amoxicillin, which was available at 83.8% of facilities in our study. 31 Similarly, cefixime is also one of the most commonly used antibiotics according to pharmaceutical sales, but was available at only 12.9% of facilities. 31 These discrepancies suggest there may be a divergence between supply and use in some countries.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal infections with highly resistant pathogens like extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae, which are considered an urgent health threat by the US Centers for Disease Control and Prevention [13], have been documented across the globe and have become increasingly prevalent over the past decade [14,15]. Children under two are also one of the likeliest age groups to receive antibiotics [16,17]. Frequent antibiotic exposures may increase the relative abundance of antibiotic resistance genes (ARGs) harbored by gut bacteria, and foster a gut environment supportive of their transfer to pathogens [4,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%